Relating defeasible and normal logic programming through transformation properties - Chesñevar, Carlos Iván (2000)
This paper relates the Defeasible Logic Programming (DeLP) framework and its semantics SEMneLP to more classical logic programming frameworks. In DeLP we distinguish between strict and defeasible rules, combining default and strict negation. In contrast to this, in normal logic programming (NLP), there is one negation nut, interpreted as a kind of negation-as-failure, which introduces defeasibility. Various semantics have been defined for NLP, notably the well-founded semantics WFS. In this paper we consider the transformation properties for NLP introduced by Brass et al. adapted within the DeLP framework. We show which transformation properties are satisfied, identifying the aspects in which NLP and DeLP differ. We contend that transformation rules presented in this paper can help to gain a better understanding of the relationship of DeLP semantics with respect to more traditional logic programming approaches. As a byproduct we get that DeLP is a proper extension of NLP